A Sodalite‐Type Silver Orthophosphate Cluster in a Globular Silver Nanocluster. (14th May 2020) - Deng, Chenglong; Sun, Cunfa; Wang, Zhi; Tao, Yunwen; Chen, Yilin; Lin, Jinqing; Luo, Genggeng; Lin, Bizhou; Sun, Di; Zheng, Lansun
Abstract: The synthesis and structure of a giant 102‐silver‐atom nanocluster (NC) 1 is presented. X‐ray structural analysis reveals that 1 features a multi‐shelled metallic core of Ag6 @Ag24 @Ag60 @Ag12 . An octahedral Ag6 core is encaged by a truncated octahedral Ag24 shell. The Ag24 shell is composed of a hitherto unknown sodalite‐type silver orthophosphate cluster (SOC) (Ag3 PO4 )8 , reminiscent of the Ag3 PO4 photocatalyst. The SOC is capped by six interstitial sulfur atoms, giving a unique anionic cluster [Ag6 @(Ag3 PO4 )8 S6 ] 6−, which functions as an intricate polyhedral template with abundant surface O and S atoms guiding the formation of a rare rhombicosidodecahedral Ag60 shell. An array of 6 linear Ag2 staples further surround this Ag60 shell. [Ag6 @(Ag3 PO4 )8 S6 ] 6− is an unusual Ag‐based templating anion to induce the assembly of a SOC within silver NC. This finding provides molecular models for bulk Ag3 PO4, and offers a fresh template strategy for the synthesis of silver NCs with high symmetry. Abstract : A giant globular 102 Ag atom nanocluster has been isolated by a templating approach. The nanocluster features an unprecedented sodalite‐type silver orthophosphate cluster (SOC) stabilized in a rare 60‐Ag rhombicosidodecahedron. This is a reminder of the key role of the SOC as a molecular analogue of the important Ag3 PO4 semiconducting material.